ANALISIS KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA DITINJAU DARI KEMAMPUAN VERBAL PADA SISWA KELAS VII SMP MUHAMMADIYAH SE-KOTA MAKASSAR - Wahyuddin Wahyuddin; Muhammad Ihsan (Suska Journal of mathematics Education, 2016)
One measure of the success of students is to look at learning outcomes of students, low ability students in working on a story about the looks of the many errors of students in doing story problems so low student mathematics achievement. There are several factors that affect the high and low ability students in doing mathematics story problems, one of which is verbal.This study aims to determine the level of verbal ability and ability to solve word problems and to investigate the effect of verbal ability to ability to solve math word problems of Grade VII Students in the Entire SMP Muhammadiyah in Makassar. This type of research is ex-post facto nature of causality. The study population was all of Grade VII Students in the Entire SMP Muhammadiyah in Makassar  scattered as many as 1048 students in 10 schools and a total sample of 145 students with a sampling technique that stratified cluster random sampling. Instruments used in this research is to test each variable with data analysis techniques used were descriptive statistics and analysis infrensial (Correlation Analysis and Regression Analysis).The results of this study indicate that: (1) The level of verbal skills of students in middle category with an average value of 51.83; (2) Level of ability to solve word problems of students in middle category with an average value of 70.62; (3) Verbal Ability has a correlation / relationship with the ability to solve math word problems with a relationship of 67.5%; (3) Verbal Ability positive effect on ability to solve word problems with the effect of 42% while the rest of 58% influenced by other variables outside the model. Verbal ability positively affects students ability to solve word problems, it can be interpreted that the better or higher verbal skills possessed by students the ability to solve word problems these students will be better or higher.